Extracellular vesicles from Trypanosoma cruzi-dendritic cell interaction show modulatory properties and confer resistance to lethal infection as a cell-free based therapy strategy - Gutierrez, Brenda Celeste; Ancarola, Maria Eugenia; Volpato-Rossi, Izadora; Marcilla, Antonio; Ramirez, Marcel Ivan; Rosenzvit, Mara Cecilia; Cucher, Marcela; Poncini, Carolina Verónica (Frontiers in Cellular and Infection Microbiology, 2022)
Extracellular vesicles (EVs) include a heterogeneous group of particles. Microvesicles, apoptotic bodies and exosomes are the most characterized vesicles. They can be distinguished by their size, morphology, origin and molecular composition. To date, increasing studies demonstrate that EVs mediate intercellular communication. EVs reach considerable interest in the scientific community due to their role in diverse processes including antigen-presentation, stimulation of anti-tumoral immune responses, tolerogenic or inflammatory effects. In pathogens, EV shedding is well described in fungi, bacteria, protozoan and helminths parasites. For Trypanosoma cruzi EV liberation and protein composition was previously described. Dendritic cells (DCs), among other cells, are key players promoting the immune response against pathogens and also maintaining self-tolerance. In previous reports we have demonstrate that T. cruzi downregulates DCs immunogenicity in vitro and in vivo. Here we analyze EVs from the in vitro interaction between blood circulating trypomastigotes (Tp) and bone-marrow-derived DCs. We found that Tp incremented the number and the size of EVs in cultures with DCs. EVs displayed some exosome markers and intracellular RNA. Protein analysis demonstrated that the parasite changes the DC protein-EV profile. We observed that EVs from the interaction of Tp-DCs were easily captured by unstimulated-DCs in comparison with EVs from DCs cultured without the parasite, and also modified the activation status of LPS-stimulated DCs. Noteworthy, we found protection in animals treated with EVs-DCs+Tp and challenged with T. cruzi lethal infection. Our goal is to go deep into the molecular characterization of EVs from the DCs-Tp interaction, in order to identify mediators for therapeutic purposes.